Forum ekspertów The role of C-reactive protein as a cardiovascular risk predictor - Boguslawski, George; Labarrere, Carlos A. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
A wealth of evidence supports the concept of inflammation playing a pivotal role in the development and progression of atherosclerosis. C-reactive protein (CRP) is a sensitive acute-phase inflammatory marker for the development of cardiovascular events such as coronary artery disease, myocardial infarction and stroke. Numerous studies indicate that CRP is not only a biomarker but also an active mediator of inflammation and atherogenesis through its direct effects on leukocytes and endothelial cells. We review the evidence and suggest mechanisms by which CRP can affect arterial endothelial cell activation, macrophage recruitment and foam cell generation and the development of atherosclerotic lesions. We emphasize the direct role of CRP in sustaining a proinflammatory and procoagulant milieu within the arterial neointima. This review also proposes that CRP can directly injure arterial endothelium and is a molecule involved in the maintenance of a systemic proatherosclerotic environment. In addition, we review therapies that target CRP for both the prevention and treatment of atherosclerotic diseases.